2017
DOI: 10.1074/jbc.m116.773200
|View full text |Cite
|
Sign up to set email alerts
|

UbMES and UbFluor: Novel probes for ring-between-ring (RBR) E3 ubiquitin ligase PARKIN

Abstract: Ring-between-ring (RBR) E3 ligases have been implicated in autoimmune disorders and neurodegenerative diseases. The functions of many RBR E3s are poorly defined, and their regulation is complex, involving post-translational modifications and allosteric regulation with other protein partners. The functional complexity of RBRs, coupled with the complexity of the native ubiquitination reaction that requires ATP and E1 and E2 enzymes, makes it difficult to study these ligases for basic research and therapeutic pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…Multi-monoubiquitination of Miro1 (Kazlauskaite et al, 2014a;Klosowiak et al, 2016) and an atypical lysine-27-mediated ubiquitin chain (Birsa et al, 2014) suggest additional roles for Miro1 ubiquitination beyond degradation. Furthermore, Park et al (2017) showed recently that Miro1 enhances Parkin catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-monoubiquitination of Miro1 (Kazlauskaite et al, 2014a;Klosowiak et al, 2016) and an atypical lysine-27-mediated ubiquitin chain (Birsa et al, 2014) suggest additional roles for Miro1 ubiquitination beyond degradation. Furthermore, Park et al (2017) showed recently that Miro1 enhances Parkin catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitin thioester probe UbFluor recapitulates the native biochemical mechanisms of E3 ligases that rely on a catalytic cysteine for covalent ubiquitin transfer, allowing continuous monitoring of ubiquitination reactions at low volumes (Krist et al, 2016; Park et al, 2017). This enables measurement of initial reaction rates for multiple PARKIN variants in combination with allosteric effector proteins and substrates.…”
Section: Basic Protocol 1 Parkin Fluorescence Polarization (Fp) Assamentioning
confidence: 99%
“…PARKIN E3 ligase, pPARKIN, or PARKIN with point mutations (available from Boston Biochem or LifeSensors and obtainable from E.coli expression) (Park et al, 2017)…”
Section: Basic Protocol 1 Parkin Fluorescence Polarization (Fp) Assamentioning
confidence: 99%
See 1 more Smart Citation
“…In these assays, the E1-and E2-functions are bypassed and Ub-thioesters [Ub-MES (Park et al 2015) or fluorescent analogue Ub-FLUOR (Krist et al 2016)] are directly trans-thiolated by the active cysteines in several E3's. The fluorescent thioester allows real-time quantitative monitoring of E3-ligase activity using a fluorescence polarization set up (Park et al 2017) (see Fig. 3d).…”
Section: Assay Reagentsmentioning
confidence: 99%